Kaznivo dejanje pranja denarja po 245. členu KZ-1 - Čop, Uroš (Podjetje in delo, 2016)
The purpose of the article is to begin a discussion on the conventional interpretation of criminal conduct set forth under the first paragraph of Article 245 of the Criminal Code (Kazenski zakonik - KZ-1). Judging from the extremely sparse case law of Slovene courts as well as my own professional experience, the detection and prosecution of money laundering offenders in Slovenia has mainly been based on "traditional" types of criminal conduct, which involves substantive components of money laundering, while their contemporary forms are scarcely present. In my own opinion, however, the provision under the first paragraph of Article 245 of KZ-1 was designed with a sufficient degree of modernity as well as broadness to allow for the prosecution and punishment of contemporary criminal conducts which have emerged in the era of internet, new payment methods (bitcoin, digital currencies and the like) and also computer games. Based on this provision it can and should be ascertained in each particular case whether the conduct of an offender has or could have led to concealment or an attempt to conceal the source of "dirty" money or property: there is therefore no reason why contemporary forms of money laundering should not be prosecuted or their offenders convicted.
Keywords: kazenske sankcije; kazniva dejanja; organizirani kriminal; pranje denarja